PENGARUH BOOK TAX DIFFERENCES TERHADAP MANAJEMEN LABA - Deni Purnama Sari; Anna Purwaningsih (Modus, 2014)
This study aims to determine the efect of book tax diferences on earnings management. The analytical method used in this study is the logistic regression analysis. The population in this research is manufacturing companies listed on the Stock Exchange started the observation period up to the year 2009-2011. Tis study uses 140 companies with purposive sampling technique.The independent variable of this research is the book tax diferences which consist of positive large book tax diferences (LPBTD) proxied by the deferred tax expense and tax negative book large diferences (LNBTD) proxied by retained tax benefts. The dependent variable in this study is earnings management proxied by income distribution approach. Te analysis showed that LPBTD positive efect on earnings management and LNBTD positive efect on earnings management.Keywords: book tax diferences, earnings management, retained tax expense, retained tax benefts.